2017
DOI: 10.3390/diseases5020013
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the MAPK Signaling, Topoisomerase and Dietary Bioactives in Controlling Cancer Incidence

Abstract: Reactive oxygen species (ROS) are common products of mitochondrial oxidative phosphorylation, xenobiotics metabolism and are generated in response to several environmental stress conditions. Some of them play important biochemical roles in cellular signal transduction and gene transcription. On the other hand, ROS are known to be involved in a wide range of human diseases, including cancer. The excessive production of such ROS together with disruption of homeostasis detoxifying mechanisms can mediate a series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 69 publications
0
18
0
Order By: Relevance
“…Various intracellular upstream signaling cascades, particularly the mitogen activated protein kinase (MAPK) pathways, regulate the production of MMP-2 and MMP-9. The major components of the MAPK pathways, the ERK, JNK, and p38 MAPK pathways, regulate cell migration, invasion, proliferation, survival, and apoptosis following different cellular signals [17, 18]. α-mangostin can modulate tumor migration and invasion by down-regulating MMP-2, MMP-9, and urokinase-type plasminogen activator (µPA) through the αvβ3 integrin receptor and the FAK/ERK/NF-κB signal pathway in lung cancer [19], by downregulating the JNK-mediated pathway and inhibition of NK-κB and AP-1 binding activity in prostate cancer [20], and by suppressing the ERK-mediated pathway and reducing AP-1 and NK-κB binding in breast cancer [21].…”
Section: Introductionmentioning
confidence: 99%
“…Various intracellular upstream signaling cascades, particularly the mitogen activated protein kinase (MAPK) pathways, regulate the production of MMP-2 and MMP-9. The major components of the MAPK pathways, the ERK, JNK, and p38 MAPK pathways, regulate cell migration, invasion, proliferation, survival, and apoptosis following different cellular signals [17, 18]. α-mangostin can modulate tumor migration and invasion by down-regulating MMP-2, MMP-9, and urokinase-type plasminogen activator (µPA) through the αvβ3 integrin receptor and the FAK/ERK/NF-κB signal pathway in lung cancer [19], by downregulating the JNK-mediated pathway and inhibition of NK-κB and AP-1 binding activity in prostate cancer [20], and by suppressing the ERK-mediated pathway and reducing AP-1 and NK-κB binding in breast cancer [21].…”
Section: Introductionmentioning
confidence: 99%
“…MEK1/2/5 specifically recognizes Erk-like MAPKs, harboring a T-E-Y motif in the activation loop, while MKK3/6as well as MKK4/7-like MAPKKs are specific for p38 (T-G-Y) and JNK-like (T-P-Y) MAPKs, respectively (15,16). Recent evidence indicates that therapies targeted toward MAPK pathway components stand out as potential alternative drugs in many tumor types (17)(18)(19).…”
mentioning
confidence: 99%
“…The MAPK signaling pathway (p38, ERK, and JNK) is involved in various cellular biological activities, such as cell proliferation, survival, and differentiation (Selim, Abdelrasoul, Aboelmagd, & Tawila, ). Previous studies showed that inhibition of the production of iNOS, COX‐2, and MMPs acted through the MAPK signaling pathway (Chen et al, ; Ma et al, ).…”
Section: Discussionmentioning
confidence: 99%